High prevalence of Rickettsia africae variants in Amblyomma variegatum ticks from domestic mammals in rural Western Kenya: Implications for human health - Maina, Alice N.; Omulo, Sylvia A.; Jiang, Ju; Cutler, Sally J.; Ade, Fredrick; Ogola, Eric; Feikin, Daniel R.; Njenga, M. Kariuki; Cleaveland, Sarah; Mpoke, Solomon; Ng'ang'a, Zipporah; Breiman, Robert F.; et al. (Mary Ann Liebert, Inc, 2015)
Tick-borne spotted fever group (SFG) rickettsioses are emerging human diseases caused by obligate intracellular Gram-negative bacteria of the genus Rickettsia. Despite being important causes of systemic febrile illnesses in travelers returning from sub-Saharan Africa, little is known about the reservoir hosts of these pathogens. We conducted surveys for rickettsiae in domestic animals and ticks in a rural setting in western Kenya. Of the 100 serum specimens tested from each species of domestic ruminant 43% of goats, 23% of sheep, and 1% of cattle had immunoglobulin G (IgG) antibodies to the SFG rickettsiae. None of these sera were positive for IgG against typhus group rickettsiae. We detected Rickettsia africae–genotype DNA in 92.6% of adult Amblyomma variegatum ticks collected from domestic ruminants, but found no evidence of the pathogen in blood specimens from cattle, goats, or sheep. Sequencing of a subset of 21 rickettsia-positive ticks revealed R. africae variants in 95.2% (20/21) of ticks tested. Our findings show a high prevalence of R. africae variants in A. variegatum ticks in western Kenya, which may represent a low disease risk for humans. This may provide a possible explanation for the lack of African tick-bite fever cases among febrile patients in Kenya.
Keywords: Ambylomma variegatum; Rickettsia africae; Tick-borne spotted fever group; African tick-bite fever